Development of the participatory protection and control model of pesticide uses among agriculturalists by the community network in Ronthong Subdistrict, Satuek District, Buri Ram Province - บุญประกอบ, อนันต์; หอมจำปา, พิศมัย; พิมพ์จันทร์, นพดล (UBRU Journal for Public Health Research, 2018)
This action research was aimed to develop the prevention and control model of pesticide uses among agriculturalists by means of the community network participation in Ronthong Sub-district, Satuek District, Buri Ram Province. The target groups included 54 agriculturalists and community network members. Data collection used questionnaire, interview guide, participation and observation checklists. Quantitative data analysis used descriptive statistics, including percentage, median, mean and standard deviation, and inferential statistics, including paired t-test. Qualitative data analysis used content analysis. Results indicated 8 steps along the model development. These steps included Prevention Model of pesticide uses by agriculturalists. These activities included: 1) Basic information of local context study; 2) Situational Analysis; 3) Participatory planning with the use of A-I-C techniques; 4) Implementation of the project activities based on plan; 5) Supporting and monitoring; 6) Observation and data collection on performance and research outputs; 7) Participatory analysis and synthesis of the research results; and 8) Organizing the meeting for lesson learned summary and exchange. Achievement of the model was evaluated in terms of knowledge and behaviors related to hazard prevention and control of pesticide uses and participation in the project of the target groups. After the model implementation, it was found that the target groups had a higher level of knowledge and practices related to hazard prevention and control of pesticide uses, as well as participation in the project activities. Consequently, their appropriate knowledge and practices of prevention and control of pesticide uses increased after the model implementation. In addition, the community network members were able to cooperatively work together to help solve the problems all steps of the research processes. Keys success factors of this study derived from application of appropriate techniques in building participation, having put value recognition toward member in the research processes, as well as consistently and strongly making local network for working together under the great supports from both government organization and community